Socio-affective relatives: legal consequences in the scope of brazilian succession law (Research, Society and Development, 2023)
This article seeks to highlight questions about affective kinship inaugurated in the country's legislation by the 1988 Constitution through the principle of human dignity and addressed more specifically in the Civil Code of 2002, which expressly mentions the possibility of kinship of civil origin. The historical content of the family will be discussed so that there is an understanding of the evolutions suffered by the institution in the Brazilian legal system, as well as an analysis using doctrine and jurisprudence as a research methodology, evidencing judgments of the Supreme Court of Justice on the subject, of the Court of Justice of Santa Catarina and Court of Justice of Rio Grande do Sul. It also seeks to analyze the position of the Federal Supreme Court in the judgment of appeal 898060. The theme problem deals with the legal consequences that come from the recognition of this type of kinship. The objective is to help in understanding the way in which the theme was primarily received in the Brazilian legal system, such as the requirements that both the majority doctrine and the aforementioned courts enshrined as necessary for the recognition of socio-affective kinship and the inheritance rights that arise from it. It should be noted that this article does not intend to deepen the study of the subject.